RUNX1 can mediate the glucose and O-GlcNAc-driven proliferation and migration of human retinal microvascular endothelial cells. Issue 1 (4th August 2021) - Xing, Xindan; Wang, Hanying; Niu, Tian; Jiang, Yan; Shi, Xin; Liu, Kun
Abstract : Introduction: This study aims to determine whether high glucose condition and dynamic O-linked N-acetylglucosamine (O-GlcNAc) modification can promote the proliferation and migration of human retinal microvascular endothelial cells (HRMECs) and whether Runt-related transcription factor 1 (RUNX1) could mediate the glucose and O-GlcNAc-driven proliferation and migration of HRMECs. Research design and methods: Western blot analysis was used to detect the O-GlcNAc modification level and RUNX1 level in cells and retina tissues, cell growth was studied by cell counting kit-8 assay, cell proliferation was detected by immunofluorescence staining. Then, cell migration and tube formation were investigated by scratch-wound assay, Transwell assay, and tube-forming assay. The changes of retinal structure were detected by H&E staining. The O-GlcNAc modification of RUNX1 was detected by immunoprecipitation. Results: High glucose increases pan-cellular O-GlcNAc modification and the proliferation and migration of HRMECs. Hence, O-GlcNAc modification is critical for the proliferation and migration of HRMECs. RUNX1 mediates the glucose and O-GlcNAc-driven proliferation and migration in HRMECs. RUNX1 can be modified by O-GlcNAc, and that the modification is enhanced in a high glucose environment. Conclusions: The present study reveals that high glucose condition directly affects retinal endothelial cells (EC) function, and O-GlcNAc modification is critical for the proliferation and migration of HRMECs, RUNX1 may take part in this mechanism, and maybe the function of RUNX1 is related to its O-GlcNAc modification level, which provides a new perspective for studying the mechanism of RUNX1 in diabetic retinopathy.